Electrical and optical properties of bulk GaN substrates studied by Kelvin probe and photoluminescence. Issue 3 (21st December 2012) - McNamara, J. D.; Foussekis, M. A.; Baski, A. A.; Li, X.; Avrutin, V.; Morkoç, H.; Leach, J. H.; Paskova, T.; Udwary, K.; Preble, E.; Reshchikov, M. A.; Toropov, Alexey; et al.
Abstract We have investigated the N‐ and Ga‐polar faces of bulk GaN substrates with photoluminescence (PL) and the surface photovoltage (SPV) technique using a Kelvin probe attached to an optical cryostat. Experiments were conducted in vacuum. Some of the surfaces were mechanically polished (MP), while others were epi‐ready after a chemical‐mechanical polish (CMP). From the SPV measurements, the band bending in a sample having both surfaces treated with the CMP method was calculated to be about 0.83 and 0.70 eV for the Ga‐ and N‐polar surfaces, respectively. The restoration of the SPV after ceasing the UV illumination showed that the SPV from CMP‐treated surfaces behaved as predicted by a thermionic model, whereas the SPV from MP‐treated surfaces restored with a much faster‐than‐predicted rate. This result can be interpreted by the hopping of charge carriers in the highly‐defective near‐surface layer of the MP‐treated samples. Remarkably, removing the top 700 nm defective layer by dry etching restored the quality of the electrical and optical properties of GaN. (© 2012 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)